PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT. INDRI PLANT PKS NAPAL KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Nadya Afrillah; Zulfadil Zulfadil (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine whether Reward and Punishment affect Employee Performance at PT. Indri Plant PKS Napal employees, both partially and simultaneously. The sample in this study was 70 respondents, using the purposive sampling method. This study uses a quantitative descriptive approach and the data analysis technique used is multiple linear regression with the help of the SPSS 26 program. The results of this study indicate that the Reward and Punishment variables affect Employee Performance both partially and simultaneously. The Adjusted R Square value of 0.614 indicates that the Reward and Punishment variables overall have an influence of 61.4% on Employee Performance, while the remaining 38.6% is influenced by other variables not examined in this study.